Disabled children in public playgrounds: a pilot study / Seyed Hassan Khalifeh Soltani, Mohamed Yusoff Abbas and Mohamad Awang. - Soltani, Seyed Hassan Khalifeh; Abbas, Mohamed Yusoff; Awang, Mohamad (Universiti Teknologi MARA Cawangan Selangor, 2018)
This is a cross-sectional pilot study on children with disabilities needs in public playgrounds. 7hey often faced problems at public playgrounds, entertainment and amusement areas, due to the lack of ample provisions to cater their special needs. 7he purpose of the study was to inuestigate the current status of infrastructure and design proper public playgrounds in Malaysia. 7he study period was six months. Ouerall 40 disabled children, parents, teachers and doctors were questioned and interuiewed. Statistical Package for the Social Science (SPSS) software program was used for analysis. 7he ßnding reuealed that there is necessary need to improue and construct well equipped public playgrounds for children with disabilities.